Employee Retention in the Service Industry in Malaysia - Zainal, Nur Syafiqah Binti; Wider, Walton; Lajuma, Surianti; Ahmad Khadri, Mohd Wafiy Akmal B.; Taib, Nasehah Mohd; Joseph, Asong (Frontiers in Sociology, 2022)
This study aims to investigate the effects of work-life balance, work environment, and reward and compensation on employee retention in Malaysia. A total of 400 questionnaires were collected online from employees within the service industry in Malaysia. Partial least square structure equation modeling was used to test the model and hypotheses. The results reveal that work-life balance and work environment had a strong positive effect on employee retention, but reward and compensation had a much stronger positive effect on employee retention. This research provides unique theoretical contributions by investigating these factors in the midst of the COVID-19 outbreak as components of the reciprocal process between employee and employer, and their effects on employee retention. This study also provides vital insights to business organisations to consider designing effective employee retention plans for a successful business.